Reactions to Participating in Intimate Partner Violence and Minority Stress Research: A Mixed Methodological Study of Self-Identified Lesbian and Gay Emerging Adults. Issue 6 (23rd July 2016) - Edwards, Katie M.; Sylaska, Kateryna M.
Abstract : The purpose of this study was to examine lesbian and gay (LG) young adults' reactions to participating in intimate partner violence (IPV) and minority stress research using a mixed methodological design. Participants were 277 U.S. college students currently involved in same-sex relationships and self-identified cisgender LG who completed an online questionnaire that included closed- and open-ended questions. Results suggested that IPV research was well tolerated by the vast majority of participants; close to one in 10 participants reported being upset by the study questions, yet 75% of upset individuals reported some level of personal benefit. Reasons for upset as identified in the open-ended responses included thinking about personal experiences with IPV, as the perpetrator or friend of a victim, as well as thinking about the uncertainty of their future with their current partner. The correlates of emotional reactions and personal benefits to research participation were also examined, and these varied among gay men and lesbian women. Implications of these findings underscore the importance of accurate reflection of risk and benefits in informed consent documents as well as systematic evaluation of sexual minority participants' reactions to research participation in an effort to conduct ethically sound sexual science research.